Immunogenicity and safety of an adjuvanted inactivated polio vaccine, IPV-Al, compared to standard IPV: A phase 3 observer-blinded, randomised, controlled trial in infants vaccinated at 6, 10, 14 weeks and 9 months of age - Bravo, Lulu C. (Vaccine, 2020)
BACKGROUND: A dose-sparing inactivated polio vaccine (IPV-Al), obtained by adsorption of inactivated virus to an aluminium hydroxide adjuvant, can help mitigate global supply and the cost constraints of IPV. The objective of this trial was to demonstrate the non-inferiority of IPV-Al to standard IPV. METHODS: This phase 3, observer-blinded, randomised, controlled trial was conducted at 5 investigational sites in the Philippines. Infants not previously vaccinated with any polio vaccines were randomised to receive three IPV-Al (n = 502) or IPV vaccinations (n = 500) at 6, 10 and 14 weeks of age plus a booster vaccination at 9 months. The primary endpoint was type-specific seroconversion, defined as an antibody titre ≥4-fold higher than the estimated maternal antibody titre and a titre ≥8, one month after the primary vaccination series. RESULTS: Seroconversion rates following primary vaccination with IPV-Al (483 infants in the per-protocol analysis set) or IPV (478 infants) were: polio type 1, 97.1% versus 99.0%; type 2, 94.2% versus 99.0%; and type 3, 98.3% versus 99.6%. IPV-Al was non-inferior to IPV, as the lower 95% confidence limits of the treatment differences were above the predefined −10%-point limit: type 1, −1.85% (−3.85; −0.05); type 2, −4.75% (−7.28; −2.52); type 3, −1.24 (−2.84; 0.13). The booster effect (geometric mean titre (GMT) post-booster / GMT pre-booster) was: type 1, 63 versus 43; type 2, 54 versus 47; type 3, 112 versus 80. IPV-Al was well tolerated with a safety profile comparable to that of IPV. Serious adverse events were recorded for 29 infants (5.8%, 37 events) in the IPV-Al group compared to 28 (5.6%, 48 events) in the IPV group. CONCLUSION: Non-inferiority of IPV-Al to IPV with respect to seroconversion was confirmed and a robust booster response was demonstrated. Both vaccines had a similar safety profile. ClinicalTrials.gov identifier: NCT03032419.